Atomically dispersed intrinsic hollow sites of M-M₁-M (M₁ = Pt, Ir; M = Fe, Co, Ni, Cu, Pt, Ir) on FeCoNiCuPtIr nanocrystals enabling rapid water redox - Lu, Yu (2022)
Fabrication of advanced electrocatalysts acting as an electrode for simultaneous hydrogen and oxygen evolution reactions (i.e., HER and OER) in an overall cell has attracted massive attention but still faces enormous challenges. This study reports a significant strategy for the rapid synthesis of high-entropy alloys (HEAs) by pulsed laser irradiation. Two types of intrinsic atomic hollow sites over the surface of HEAs are revealed that enable engaging bifunctional activities for water splitting. In this work, a novel senary HEA electrocatalyst made of FeCoNiCuPtIr facilitates the redox of water at only 1.51 V to achieve 10 mA cm−2 and still remains steadily catalytic and durable after being subjected to a 1m KOH solution for more than 20 h. First-principles calculations reveal that the incorporation of Ir and Pt atoms with neighboring elements donate valence electrons to hollow sites weakening the coupling strength between adsorbate and alloy surface and, consequently accelerating both HER and OER. This work delivers a powerful technique to synthesize highly efficient HEA catalysts and unravels the formation mechanism of active sites across the surface of HEA catalysts.